Increased autumn and winter precipitation during the Last Glacial Maximum in the European Alps - C. Spötl (Nature Portfolio, 2021)
What controlled changes of glaciers in the European Alps at the time of their largest extent, about 25,000 years ago, is not well known. Here, the authors use cryogenic carbonates in caves to show that heavy snowfall during autumn and early winter was the main source of glacier growth.